2009
DOI: 10.1063/1.3095812
|View full text |Cite
|
Sign up to set email alerts
|

Submonolayer quantum dot infrared photodetector

Abstract: We describe the concept of the submonolayer quantum dot infrared photodetector (SML QDIP) and report experimental device results on long-wavelength infrared detection. An SML QDIP structure was fabricated into megapixel focal plane arrays, which produced clear infrared images up to 80 K. Detectors in the focal plane showed a responsivity peak at 7.8 μm and noise equivalent temperature difference of 33 mK at 70 K.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(37 citation statements)
references
References 23 publications
0
37
0
Order By: Relevance
“…Research in QDIP has seen rapid progress in recent years, with FPA results reported by several groups [6,7]. Variations in the basic QDIP structure, including the dot-in-the-well (DWELL) [6] and the confinement enhanced have resulted in increased versatility and improved performance.…”
Section: Megapixel Lwir Sml Qdip Focal Plane Arraymentioning
confidence: 97%
“…Research in QDIP has seen rapid progress in recent years, with FPA results reported by several groups [6,7]. Variations in the basic QDIP structure, including the dot-in-the-well (DWELL) [6] and the confinement enhanced have resulted in increased versatility and improved performance.…”
Section: Megapixel Lwir Sml Qdip Focal Plane Arraymentioning
confidence: 97%
“…Sub-monolayer quantum-dot heterostructures [31,44] are most promising for the realization of a class D laser with strong inhomogeneous broadening. Other possibilities are solid-state matrices with active centers [14,35] and molecular j-and h-aggregates [4,32,36].…”
Section: Two Types Of Media With Extreme Spatial-spectral Density Of mentioning
confidence: 99%
“…The image on the left is taken at 45 K, and shows very good dynamic contrast. The image on the left is taken at 80 K. More details of our work on the SML QDIP are reported elsewhere [12].…”
Section: Submonolayer Quantum Dot Infrared Photodetectormentioning
confidence: 99%